Analisis Perbandingan Keputusan Pendanaan Berbasis Ekuitas dan Sukuk dalam Perspektif Prinsip Syariah pada Perusahaan di Indonesia - Puji Ayuni Anawawi; Indi Isnandini Fajrin; Reza Adiethya Nugraha; Joni Joni (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2026)
This study aims to analyze the comparison of equity-based financing decisions and sukuk from the perspective of Sharia principles in companies in Indonesia. The development of the Islamic capital market in Indonesia shows a significant increase in the use of financing instruments that comply with Islamic principles, thereby encouraging companies to consider funding alternatives that are not only financially efficient but also Sharia-compliant. In the framework of Sharia financial management, capital structure decisions must consider the prohibition of usury, the principle of risk sharing, fairness in risk distribution, and contract certainty. This research uses a qualitative approach with a literature study method thru the analysis of various scientific journals, regulations, and academic sources related to capital structure theory, the concept of Sharia equity, and the characteristics of corporate sukuk in Indonesia. The study results indicate that equity-based financing provides flexibility in capital structure and reflects a risk-sharing mechanism, but it has the potential to cause ownership dilution. Meanwhile, sukuk offers asset-based financing with a clear contractual structure and does not dilute company ownership, although it requires an underlying asset and a more complex issuance process. Comparatively, both instruments have Sharia legitimacy as long as they meet the screening requirements and contract structures applicable in Indonesia. This research emphasizes that corporate financing decisions in Indonesia need to consider the balance between financial efficiency and compliance with Sharia principles.